Repelling mosquito / Muhamad Dan Darrawi Sadli, Mohd Ierokie Pauzi and Muhamad Adnan Arif A.Rahman - Sadli, Muhamad Dan Darrawi; Pauzi, Mohd Ierokie; A.Rahman, Muhamad Adnan Arif (2015)
This project represents as the one method to decreasing the number of mosquito. This device is called as Repelling Mosquito. The repelling Mosquito is using air pump to produce air bubble which will create a ripple. The device is supported with panel solar which is the main source of the device. However, the device needs a backup source which is internal battery. The battery inside the device is active during the night as the solar panel is useless during night. This circuit also has been improvising with another circuit which is called as Running Light. This running light is functioning as indicator light which show the user that the device is active or not. Running Light is using 4 IC which is IC 555, IC 7400 NAND Gate, 1-tolO Decoder 7493 IC and l-tol6 Decoder 7442 IC. The running light will light in sequence according to the IC l-to-16 Decoder. When the switch is on, the solar panel will absorb the solar flare and convert into electrical energy and this energy will split into 2 works. First it will go to the main circuit which is repelling circuit, and it will activate the air pump to produce the ripple. And the second one will go to the running light circuit. This process will go on until the main switch is turn off.